Study Result of Mongolian Natural Wild Seabuckthorn (Hippophae rhamnoides L.) - D., Oyungerel; G., Bayaraa; S., Battumur; G., Altangoo; D., Nasanjargal; D., Gantuya; T. S. , Otgontamir (International Journal For Research In Agricultural And Food Science, 2019)
Seabuckthorn sub specie (Hippophae rhamnoides L. ssp mongolica Rous.) is distributed in confluence of Orkhon-Selenge and basins of Zavkhan Tes, Uvs Tes, Bukhmurun, Tortkhilog Buyant, Khovd, Zavkhan, Borkh and Bulgan rivers. Natural wild seabuckthorn’s permanent distribution is in the western part of Mongolia’s mountainous region of Altai, Khangai and at the Tes, Zavkhan and Khovd rivers with internal flow to Great Lake concave, which starts from Altai and Khangai ranges’ branch mountains and at the Bulgan and other rivers’ valley, which have an external flow. By natural and weather condition, Bulgan aimag is located in humid cool, Selenge aimag is in arid cool, Zavkhan aimag is in arid coolish, Govi-Altai and Khovd aimags are in very arid, Uvs aimag is in arid cool region, respectively. Soil humus was in 0-20 sm depth 1.1-2.3%, 20-40 sm depth 0.6-1.7% at the research area. Soil of Zavkhan river basin had lowest humus content (0.76-1.2%), this includes Mongolian sand area and areas with sandy soil. Frame of this study included 18 soums of Selenge, Bulgan, Zavkhan, Govi-Altai, Khovd aimags along six big river basins and revealed resource of 13.5 thousand hectare coverage by Mongolian natural wild seabuckthorn and conducted a mapping. Fruits biochemical analysis was done by oil, vitamin C, sugar content in types of natural population. Analyze result were classified into three groups such as high, medium and low. Oil content was fluctuated between 3.1-4.0% oil content in average 3.5%, sugar 6.0-8.9%, vitamin C content was medium in research sample types. To compare fruit colors with pulp oil and sugar content, fruits with higher content of sugar have from orange to bright yellow color and fruits with higher content of oil have red color. This is explained by synthesis of bio active substance, which belongs to carotenoid group, in the cell of fruit skin. 50-87.6% of total natural wild seabuckthorn has below 10 years age, 13-50% has 10-18 age. Selected 21 forms were taken local MK numbers, registered according to International cultivars, stored in the genebank of the PAI.